For Liberty, Bread, and Love: Annie Buller, Beckie Buhay, and the Forging of Communist Militant Femininity in Canada, 1918-1939 - Toews, Anne Frances (Simon Fraser University, 2009)
During the interwar years, friends Annie Buller and Beckie Buhay established careers with the Communist Party of Canada and forged a uniquely Communist militant femininity that led to their eventual canonization by the Party as ideal comrades. Using a biographical approach to women’s working-class history, this thesis examines these women’s significant contributions to the CPC’s political project as gendered work. It also demonstrates that although their representation of themselves as comrades was organized around their understanding of themselves as workers, it was shaped too by particularities of ethnicity, gender, and other factors that were all subsumed in the Party’s egalitarian rhetoric. Additionally, in exploring how their lifelong friendship supported their construction of Communist militant femininity, and thus enabled their work, this thesis contributes to a developing historiography of friendship that focusses on its work rather than its nature, and that is inclusive of the friendships of working-class women.
Keywords: Friendship; Labour College; communist; comrade; militant; woman question